Sentimental and Behavioral Strategies for Show-off Treatment in the Moral Education of the Holy Quran - omid Qorbankhani; Seyyed Mahmud Tayyeb Hoseyni; Mohsen Rafat (اخلاق وحیانی)
Show-off is one of the most prominent socio-cultural problems of the present age, which in addition to its opposition to religious values ​​and its evil effects in the hereafter, also has adverse economic, educational, psychological and sociological consequences in the life of this world. The Holy Quran, as a program to guide human beings from darkness to light and from vices to virtues, fought against this immoral-social vice and purified the society of the age of revelation from boastful behaviors and, on the contrary, replaced it with virtues such as equality, compassion, self-sacrifice, forgiveness and humility. Considering the importance of extracting Quranic methods in solving social problems, the present article examines the treatment strategies of show-off from the perspective of the Holy Quran in two areas of sentiment and behavior with a descriptive-analytical approach. According to the findings of the study, the sentimental strategies of Quran for show-off treatment can be divided into two parts: warning and encouragement, the former includes two methods of instruction and threat, and the latter includes the three methods of encouragement, patterning and speed and overtaking. Behavioral strategies are also divided into negative and positive, that the call for patience, humility and replacement of the factor of happiness are put under the positive strategy and the prohibition of arrogance, despair and intoxication with the possibilities under the negative strategy.